The employment contract in the current Peruvian legislation - Arévalo Vela, Javier (2021)
This article studies the employment contract and its regulation within the Peruvian legal system, taking into account legislation, doctrine and jurisprudence. Thus, we will review the main aspects of this institution, such as its definition, the subjects of the employment contract, the elements, the duration, the difference of this with other contracts, the nullity of the employment contract, the characters of the employment contract, and among other concepts.